Development and characterization of non-oxide ceramic composites for mechanical and tribological applications - Silvestroni, Laura <1981> (Alma Mater Studiorum - Università di Bologna, 2009)
The main reasons for the attention focused on ceramics as possible structural materials are their wear resistance and the ability to operate with limited oxidation and ablation at temperatures above 2000°C. Hence, this work is devoted to the study of two classes of materials which can satisfy these requirements: silicon carbide -based ceramics (SiC) for wear applications and borides and carbides of transition metals for ultra-high temperatures applications (UHTCs). SiC-based materials: Silicon carbide is a hard ceramic, which finds applications in many industrial sectors, from heat production, to automotive engineering and metals processing. In view of new fields of uses, SiC-based ceramics were produced with addition of 10-30 vol% of MoSi2, in order to obtain electro conductive ceramics. MoSi2, indeed, is an intermetallic compound which possesses high temperature oxidation resistance, high electrical conductivity (21·10-6 Ω·cm), relatively low density (6.31 g/cm3), high melting point (2030°C) and high stiffness (440 GPa). The SiC-based ceramics were hot pressed at 1900°C with addition of Al2O3-Y2O3 or Y2O3-AlN as sintering additives. The microstructure of the composites and of the reference materials, SiC and MoSi2, were studied by means of conventional analytical techniques, such as X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (SEM-EDS). The composites showed a homogeneous microstructure, with good dispersion of the secondary phases and low residual porosity. The following thermo-mechanical properties of the SiC-based materials were measured: Vickers hardness (HV), Young’s modulus (E), fracture toughness (KIc) and room to high temperature flexural strength (σ). The mechanical properties of the composites were compared to those of two monolithic SiC and MoSi2 materials and resulted in a higher stiffness, fracture toughness and slightly higher flexural resistance. Tribological tests were also performed in two configurations disco-on-pin and slideron cylinder, aiming at studying the wear behaviour of SiC-MoSi2 composites with Al2O3 as counterfacing materials. The tests pointed out that the addition of MoSi2 was detrimental owing to a lower hardness in comparison with the pure SiC matrix. On the contrary, electrical measurements revealed that the addition of 30 vol% of MoSi2, rendered the composite electroconductive, lowering the electrical resistance of three orders of magnitude. Ultra High Temperature Ceramics: Carbides, borides and nitrides of transition metals (Ti, Zr, Hf, Ta, Nb, Mo) possess very high melting points and interesting engineering properties, such as high hardness (20-25 GPa), high stiffness (400-500 GPa), flexural strengths which remain unaltered from room temperature to 1500°C and excellent corrosion resistance in aggressive environment. All these properties place the UHTCs as potential candidates for the development of manoeuvrable hypersonic flight vehicles with sharp leading edges. To this scope Zr- and Hf- carbide and boride materials were produced with addition of 5-20 vol% of MoSi2. This secondary phase enabled the achievement of full dense composites at temperature lower than 2000°C and without the application of pressure. Besides the conventional microstructure analyses XRD and SEM-EDS, transmission electron microscopy (TEM) was employed to explore the microstructure on a small length scale to disclose the effective densification mechanisms. A thorough literature analysis revealed that neither detailed TEM work nor reports on densification mechanisms are available for this class of materials, which however are essential to optimize the sintering aids utilized and the processing parameters applied. Microstructural analyses, along with thermodynamics and crystallographic considerations, led to disclose of the effective role of MoSi2 during sintering of Zrand Hf- carbides and borides. Among the investigated mechanical properties (HV, E, KIc, σ from room temperature to 1500°C), the high temperature flexural strength was improved due to the protective and sealing effect of a silica-based glassy phase, especially for the borides. Nanoindentation tests were also performed on HfC-MoSi2 composites in order to extract hardness and elastic modulus of the single phases. Finally, arc jet tests on HfC- and HfB2-based composites confirmed the excellent oxidation behaviour of these materials under temperature exceeding 2000°C; no cracking or spallation occurred and the modified layer was only 80-90 μm thick.